Urothelial Differentiation of Human Umbilical Cord-Derived Mesenchymal Stromal Cells In Vitro - Shuai Wu; Zhongliang Cheng; Guohua Liu; Xinfeng Zhao; Liang Zhong; Yingjian Zhu; Jiang Zhu (Analytical Cellular Pathology)
Human umbilical cord-derived mesenchymal stromal cells (hUCMSCs) are the most primitive of those isolated from other post-natal tissue source. The hUCMSCs possess the capability of differentiating along multi-lineage. This study aimed to investigate whether hUCMSCs can differentiate into urothelium-like cells. The hUCMSCs were isolated from fresh human umbilical cord postpartum and expanded at least to passage 3 in vitro. Subsequently, they were cultured with conditioned medium from urothelial cells (UC-CM) supplemented with 20 ng/ml exogenous epidermal growth factor (EGF). Urothelial cell specific marker uroplakin II (UPII) and cytokeratins were evaluated by reverse transcriptase-polymerase chain reaction (RT-PCR) and immunofluorescence technology. During culture, hUCMSCs started to express UPII and cytokeratins weakly at 7 days and were significantly up-regulated at 2 weeks post-induction. Additionally, morphology of hUCMSCs changed from spindle-shape to a polygonal epithelial-shape similar to that of urothelial cells after 7 days. The study results indicated that hUCMSCs can differentiate into urothelium-like cells in a defined micro-environment in vitro constituted by UC-CM and exogenous EGF.